Aspectos demográficos, clínicos, hematológicos e soroprevalência de Anaplasma phagocytophilum em cães de um abrigo no município de Lavras, Minas Gerais - Colocho, Raisa Abreu Bragança (2021)
Dogs are very important to society from an affective, social and epidemiological point of view. Despite this, the cases of mistreatment and abandonment of pets on the streets are increasing, a situation that negatively affects the animal and public health. Among the diseases with zoonotic potential that affect dogs is granulocytic anaplasmosis, caused by Anaplasma phagocytophilum. Given the scarcity of studies on granulocytic anaplasmosis in Brazil, the aim of this study was to analyze the demographic, clinical and hematological aspects of a canine population from a shelter located in the municipality of Lavras, Minas Gerais, Brazil, as well as to determine the seroprevalence of A. phagocytophilum in this population. All animals residing in the shelter were identified with microchips and clinically evaluated by veterinarians using their own forms with demographic and clinical data. Whole blood and serum samples were collected from 329 dogs from July to August 2019 and from 310 dogs between January and February 2020. Clinical samples were used for complete blood count (hematological data) and investigation of anti-A.phagocytophilum antibodies through the Indirect Immunofluorescence Reaction, this only for samples from the first sampling. Qualitative variables were analyzed from the distribution of frequencies and contingency tables, and for all quantitative variables, the mean, standard deviation, median and interquartile range were determined, in addition to their categorization. Reactive sera with titers ≥ 40 were considered positive for Anaplasma spp., while reactive sera with titers ≥ 320 were considered positive for A. phagocytophilum. The results showed that most of the dogs in the shelter were of undefinited race, all being vaccinated with anti-rabies and multiple [100% (319,50)], dewormed [100% (319,50)] and the majority neutered [98,59% (315,00)], with the predominance of adult animals [86,51% (276,00)], short-haired [67,51% (216,00)], normal body condition [65,57% (209,50)], medium size [62,57% (200,50)] and females [62,36% (199,50)]. The main clinical changes observed were dogs with lymphadenomegaly [38,69% (124,00)], skin lesion [31,50% (101,00)], body condition - overweight [23,32% (74,50)] and obese [6,07% (19,50)], increased temperature [17,05% (55,00)] and presence of ear secretion [15,72% (49,50)]. Regarding hematological alterations, were observed thrombocytopenia [36,31% (99,00)], leukopenia [15,92% (51,00)], anemia with decreased hemoglobin values [10,60% (34,00)], hematocrit [9,70% (31,00)], red blood cells [5,14% (16,50)]. Serological evaluation detected 40,12% (132/329) (95%CI: 34,78% - 45,64%) of the reactive animals with titer ≥ 40 and 4,56% (15/329) (95%CI: 2,57% - 7,41%) with titer ≥ 320, determining the seroprevalence of anti-Anaplasma spp. and anti-A. phagocytophilum antibodies in the canine population of the shelter, respectively. In conclusion, most of the canine population at the shelter was apparently healthy, but a significant portion was overweight, had skin lesions, and clinical and hematological changes that point to the need for changes in the health management of the aspects verified, especially in the early diagnosis of zoonotic diseases. It was also observed the existence of few seropositive animals for A. phagocytophilum, with the most frequent clinical-hematological aspect in these dogs being lymphadenomegaly, skin lesion, increase in temperature and thrombocytopenia.